Evaluation of two enzyme-linked immunosorbent assays for the detection of antibodies against equine arteritis virus - BANNAI, Hiroshi (J Equine Sci, 2018)
In order to establish an efficient system for serological diagnosis of equine viral arteritis in Japan, we compared enzyme-linked immunosorbent assays (ELISAs) provided by two manufacturers (Nisseiken Co., Ltd., Tokyo, Japan, and VMRD Inc., Pullman, WA, U.S.A.) by testing a series of horse sera. The results revealed that 159 of 160 virus-neutralizing (VN) antibody-positive serum samples were positive in both the Nisseiken-ELISA and VMRD-ELISA. Of the VN-negative sera (n=157), 134 and 154 samples were negative in the Nisseiken-ELISA and VMRD-ELISA, respectively. Sensitivity was 99.4% for both the Nisseiken-ELISA and VMRD-ELISA. The specificity of the VMRD-ELISA (98.1%) was significantly higher than that of the Nisseiken-ELISA (85.4%, P<0.05). The diagnostic performance of the VMRD-ELISA was superior to that of the Nisseiken-ELISA because of this greater specificity.